Teachers’ Perceptions and Experiences with Translanguaging Implementation in Rural EFL Classrooms: A Case Study from Indonesia - La Ode Rasmin; Syarifuddin Dollah; Amirullah Abduh (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
This study explores teachers' perceptions and experiences implementing translanguaging strategies in rural English as a Foreign Language (EFL) classrooms in south Buton, Indonesia. This research is a case study where the limit of this research is to focus on teacher perceptions and experiences in implementing translanguaging in English language learning in three secondary schools in rural areas in South Buton, Indonesia. The subjects of this research were three English teachers at three different schools in South Buton. This subject is expected to provide an overview of teachers' perceptions and experiences in implementing translanguaging in some rural schools in an Indonesian context. Data was collected through in-depth interviews and class observation with three experienced EFL teachers at three rural junior high schools in South Buton. The findings reveal that teachers perceive translanguaging as effectively enhancing students' learning comprehension, and the use of translanguaging can create inclusive and culturally responsive learning in EFL classrooms. The study highlights predominantly positive attitudes towards translanguaging, with teachers perceiving it as an effective tool for facilitating learning in linguistically diverse classrooms. Teachers report positive experiences, citing improved student understanding, increased engagement, and preservation of linguistic and cultural identities. The teachers' experience actively incorporated translanguaging strategies, using code-switching between English, Indonesian, and the local Cia-Cia language to enhance student comprehension. While acknowledging challenges such as balancing multiple languages and potential impacts on English proficiency development, teachers remain confident in translanguaging's effectiveness. This research is expected to contribute to the growing literature on translanguaging in EFL contexts and offer insights for educators in linguistically diverse settings.